Airlangga: His Relations to Kings in South and South-East Asia - Susanti, Ninie (UI Scholars Hub, 2013)
After 1,000 years of C.E, it was the most crucial period in the journey of Southeast Asian ancient history. Many fundamental transitions happened, which were caused by disturbances from the outside of the Southeast Asian countries, as well as, from the countries within Southeast Asia. Casparis was a scholar who wrote about King Airlangga’s rule in Java (1019 – 1043 C.E) and who called him “A True Personality” because he succeeded in helping his people going through difficult times when the state faced devastation. Coedès placed Airlangga in a position equal to that of other kings of mainland Southeast Asia, such as King Suryawarman (who ruled Khmer from 1002 to 1050), and King Aniruddha of Pagan (1044 – 1077). The content of King Airlangga’s inscriptions reflected his broad networks in politics, economy, and religion to many kings in Southeast Asia. Furthermore, his reforming ideas was – believed – inspired by his networks. During his ruling period, his ideas of reformation had granted him as a great king. He managed to raise his kingdom from the devastation caused by Pralaya in 1016 by using as an analogy, a policy which was formed through the political, economic and religious conditions implemented by other neighboring kings, to his domestic problem. The result of which is that it was an intense relationship between the kings in Southeast Asia and South Asia and King Airlangga during the spice route network and other products. This relationship continued until Majapahit era in Java, according to the inscriptions.